Differentiation of Penaeus vannamei from different thermal processing methods in physico-chemical, flavor and sensory characteristics - Liang, Rui; Lin, Songyi; Chen, Dong; Sun, Na (Food chemistry, 2022)
•Quality characteristics of shrimp samples were closely associated with water status.•Partial-least-square regression model showed better prediction for quality.•Shrimp samples after steaming + roasting had a higher level of taste.•Volatile compounds significantly increased during thermal processing. Differentiation in physico-chemical, flavor and sensory characteristics of shrimps (Penaeus vannamei) after direct roasting (DR, 200 °C), boiling (100 °C/2 min) + roasting (BR), steaming (100 °C/2 min) + roasting (SR) and microwaving (280 W/2 min) + roasting (MR) was investigated. BR, SR, and MR endowed shrimps with better texture to varying degrees and significantly (P < 0.05) increased lightness when compared to DR, which closely related to their different water status. High correlations between nuclear magnetic resonance data and quality properties were found by partial-least-squares regression (PLSR). Shrimps possessed by SR significantly (P < 0.05) increased the proportion of sweet amino acids (63.89 ± 0.92%), with superior umami and richness detected by electronic tongue. Compared with DR, both SR and MR endowed shrimps with richer ester, while BR endowed shrimps with richer hydrocarbons. Roasting combined with other thermal processing would favor improving the quality of shrimp products.